1997
DOI: 10.1002/food.19970410609
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the natural mutagenic compound safrole in spices by cooking and irradiation

Abstract: Safrole was determined using gas-liquid chromatography in some common spices as star anise, cumin, black pepper and ginger. Safrole concentration in these spices was 9,325, 3,432, 955 and 500 mg.kg-1, respectively. Black pepper was chosen to use in the following experiments. Using Ames-test with Salmonella TA 98 and TA 100 proved high cytotoxic effects due to pure safrole and black pepper volatile oil in both of them. The degradation of safrole was obvious after drying of the washed seeds of black pepper espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 6 publications
1
8
0
1
Order By: Relevance
“…In addition, safrole, a member of benzodioxoles, shows carcinogenic activities and is present naturally in essential oils of spices including black pepper, cumin, ginger, etc. Thermal treatments such as drying (70 °C, 30 min) or boiling (5 min) during cooking could decrease dose of safrole to a safer level [272]. Besides, several compounds with anti-platelet effects from garlic, black cumin, ginger, fenugreek and turmeric might lead to excess bleeding in patients with bone marrow suppression [273,274,275].…”
Section: Side Effects Of Active Compounds From Spicesmentioning
confidence: 99%
“…In addition, safrole, a member of benzodioxoles, shows carcinogenic activities and is present naturally in essential oils of spices including black pepper, cumin, ginger, etc. Thermal treatments such as drying (70 °C, 30 min) or boiling (5 min) during cooking could decrease dose of safrole to a safer level [272]. Besides, several compounds with anti-platelet effects from garlic, black cumin, ginger, fenugreek and turmeric might lead to excess bleeding in patients with bone marrow suppression [273,274,275].…”
Section: Side Effects Of Active Compounds From Spicesmentioning
confidence: 99%
“…Pharmacological investigations showed that essential oil of CC possessed a wide variety of effects including antioxidant [5,6], antimicrobial [2,3], anti-inflammatory [7,8], anticancer [9], antidiabetic [10][11][12][13], anxiolytic [14], vasodilatory [15] and estrogenic activities [16]. Although CC has long been regarded as a safe material, some toxic effects have also been reported [4,[17][18][19][20] and the toxic ingredient mainly point to safrole which has mutagenic, cancerogenic and genotoxic effects [21][22][23]. Therefore, chemical analysis of CC is very important for ensuring its clinical safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…6 Safrole is also present in other spices (e.g., star anise, cumin, nutmeg, mace, black pepper, ginger) as well as betel quid ( Piper betle infl orescence). 7,8 Methylsafrole (myristicin) is the major aromatic ingredient of nutmeg and mace. Isosafrole (4propenyl -1,2 -methylenedioxybenzene) is an isomer of safrole that occurs in the essential oil of ilang -ilang from the Philippines and in the fruit of Japanese star anise.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…8 Safrole is a clear, colorless to slightly yellow liquid with an aromatic odor of sassafras. This compound is water insoluble.…”
Section: Physiochemical Propertiesmentioning
confidence: 99%